Big Data and Security: A Review of Social Media Risks and Insights for Indonesia - Harakan, Ahmad; Abdillah, Abdillah; Said, Try Gustaf; Mujizatullah, Mujizatullah; Gray, Simon (Journal of Governance and Public Policy, 2024)
This article explores the intricacies of big data and its relationship with security, with the aim of mitigating potential security threats arising from social media platforms. The subsequent aim entails generating optimal strategies to propose to governmental entities for enhancing their efficacy in addressing security concerns pertaining to social media and its intersection with security. The present study commences by conducting a comprehensive survey of existing literature pertaining to social media security concerns and corresponding strategies for mitigating these issues. After conducting a comprehensive investigation, several significant discoveries were made and subsequently presented to aid stakeholders in better mitigating social media security risks. Numerous nations exist wherein the dynamics of government practices lack a robust social media security policy, and they exhibit skepticism towards endeavors aimed at constructing an efficient plan to mitigate social media security concerns. This study provides an overview of the existing arguments found in the literature and presents recommendations aimed at mitigating concerns related to social media security and technology. The present study also draws upon a comprehensive body of literature to identify and condense practical lessons. Further investigation and scholarly examination are necessary to explore strategies and pragmatic perspectives aimed at mitigating the potential risks associated with social media for the Indonesian government.